2020
DOI: 10.1055/a-1272-3788
|View full text |Cite|
|
Sign up to set email alerts
|

Impact of the COVID-19 pandemic on gastrointestinal endoscopy in the Netherlands: analysis of a prospective endoscopy database

Abstract: Background COVID-19 has dramatically affected gastrointestinal endoscopy practice. We aimed to investigate its impact on procedure types, indications, and findings. Methods We retrospectively analyzed endoscopies performed in 15 Dutch hospitals by comparing periods 15 March to 25 June of 2019 and 2020 using the prospective Trans.IT database. Results During lockdown in 2020, 9776 patients underwent endoscopy compared with 19 296 in 2019. Gastroscopies decreased by 57 % (from 7846 to 4467) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
84
1
9

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(104 citation statements)
references
References 12 publications
10
84
1
9
Order By: Relevance
“…The decreased activity has been reported in several studies. 5 , 6 , 7 Our results are consistent with results of other recent studies. 8 The novelty of our current report is the analysis of the post-COVID lockdown activity, which raises a public health concern.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The decreased activity has been reported in several studies. 5 , 6 , 7 Our results are consistent with results of other recent studies. 8 The novelty of our current report is the analysis of the post-COVID lockdown activity, which raises a public health concern.…”
Section: Discussionsupporting
confidence: 93%
“…Similarly, Latinga et al reported a 44% decrease in endoscopy activity after the onset of COVID-19 for colorectal cancer screening in the Netherlands. 6 …”
Section: Introductionmentioning
confidence: 99%
“…In the study from the Netherlands, the absolute number of newly diagnosed suspected gastrointestinal cancers during lockdown was approximately 35 % lower compared with the previous year [1]. The decline was restricted to esophageal and colon cancers, while the number of suspected rectal and gastric cancers remained similar.…”
mentioning
confidence: 84%
“…In this issue of Endoscopy , two studies from Europe highlight potential areas of improvement in our endoscopy practice 1 2 . A 15-center study from the Netherlands 1 and a 5-center study from Northern Italy 2 examined volume, indication, and findings of endoscopic procedures during the COVID-19 lockdown period between March and May 2020 compared with the same period in 2019. Both studies found a major decline of approximately 50 % in the volume of endoscopy procedures.…”
mentioning
confidence: 99%
See 1 more Smart Citation